Studi didactic transposition: Eksplorasi knowledge to be taught pada limit fungsi - Rini Sulastri (Journal of Didactic Mathematics, 2023)
The purpose of this research is to describe the analysis of knowledge to be taught on limit of function. This research is part of the didactic transposition research on the concept of limit of function which consists of four stages. Qualitative research with descriptive method is used in this study. The target is a differential calculus course taught in the first semester at a university in Aceh. Data collection techniques consist of documentation studies and unstructured interviews. Analysis of calculus text book documents, especially on limit functions, was carried out using a praxeology approach. The results of the analysis show that the description of the differential calculus course contains material on the real number system, functions and graphs, limits of functions, continuity of functions, derivatives of functions, and applications of derivatives. This is different from the presentation of material in RPS which is compiled by a team of lecturers supporting differential calculus courses. For presentation of material in calculus textbooks, the concept of the limit of a function begins with an intuitive or informal introduction to the concept. Several cases are given to deepen the concept of limits through graphs, analytics, and numbers.